A Framework for Improving Sales Process - Wright, Brian Michael (2013)
Aim – This management project and research is motivated by a request from the managing director of the case study company to review and assess its sales process through an empirical investigation. Using process design and analysis methodology to evaluate current company practices, this dissertation will describe the existing sales process, identify problem areas and suggest a framework for development of the sales process. It is not the intention of this management project to solve the company’s problem; merely to suggest potential actions the company could take to solve problems itself, should it choose to do so.